2023
DOI: 10.1063/5.0143253
|View full text |Cite
|
Sign up to set email alerts
|

Swinging between shine and shadow: Theoretical advances on thermally activated vibropolaritonic chemistry

Abstract: Polariton chemistry has emerged as an appealing branch of synthetic chemistry that promises mode selectivity and a cleaner approach to kinetic control. Of particular interest are the numerous experiments in which reactivity has been modified by virtue of performing the reaction inside infrared optical microcavities in the absence of optical pumping; this effort is known as “vibropolaritonic chemistry.” The optimal conditions for these observations are (1) resonance between cavity and reactive modes at normal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 139 publications
0
11
0
Order By: Relevance
“…Strong light–matter coupling between a molecular system and the electromagnetic field of an optical cavity offers new possibilities to modify chemical reactivity and selectivity, as demonstrated in recent experiments. A particularly intriguing but not yet fully understood situation occurs when a cavity mode is strongly coupled to molecular vibrations, called vibrational-strong coupling (VSC). For VSC the rate constants of ground state reactions can be modified even without external driving, i.e., without explicitly adding photons to the cavity. Probably one of the most striking features observed in such experiments is the change of the vibrational spectra due to the formation of molecular vibrational polaritons, hybrid states that involve both cavity modes and vibrational modes of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Strong light–matter coupling between a molecular system and the electromagnetic field of an optical cavity offers new possibilities to modify chemical reactivity and selectivity, as demonstrated in recent experiments. A particularly intriguing but not yet fully understood situation occurs when a cavity mode is strongly coupled to molecular vibrations, called vibrational-strong coupling (VSC). For VSC the rate constants of ground state reactions can be modified even without external driving, i.e., without explicitly adding photons to the cavity. Probably one of the most striking features observed in such experiments is the change of the vibrational spectra due to the formation of molecular vibrational polaritons, hybrid states that involve both cavity modes and vibrational modes of molecules.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, the dark states are roughly 10 6 to 10 10 times more populated than the polariton states, so the mechanism suggested here will likely not be operative . In fact, many existing works have concluded that, as per transition-state theory, enhancement of adiabatic reaction rates in the absence of optical pumping cannot occur. , …”
Section: Many Molecules In a Cavity: Tls And Beyondmentioning
confidence: 82%
“…[23][24][25][26] However, several theoretical studies, that account for the large number of molecules coupled to the cavity, suggest that SC could be rendered less effective in the collective regime owing to the entropic penalty from the dark states. 6,27,28 For enhanced polaritonic effects, the state-ofthe-art is either to use polariton condensates 29,30 or to achieve single-molecule SC. 31 In the electronic regime, both polariton condensation [32][33][34][35] and single-molecule SC 31,[36][37][38] have been achieved.…”
Section: Introductionmentioning
confidence: 99%